OzoNews Volume XIX - 30 May 2019 - United Nations Environment Programme (2019)
In this issue: 1. World Refrigeration Day. Get ready. Something really "cool" is coming 2. Four things you should know about sustainable cooling 3. ASHRAE launches new refrigeration webpage 4. A warming Arctic produces weather extremes in our latitudes 5. Namibia ratifies Kigali amendment to protect ozone layer 6. Botswana fights importation of illegal ozone depleting substances 7. Capacitan técnicos del sector refrigeración y aires acondicionados sobre refrigerantes naturales (Costa Rica) 8. Washington State Passes Climate Bill to Restrict Certain Uses of HFCs 9. Vermont Joins HFC Phase-Down Club 10. Data in the driver’s seat: leak patterns in observed data and how it can help reduce emissions - US EPA GreenChill upcoming webinar 11. Increase in CFC-11 emissions from eastern China based on atmospheric observations 12. Online administrative procedures includes ODS import license (Vietnam) 13. Flammable refrigerants: The International Electrotechnical Commission approves the charge increase in commercial refrigeration 14. Meeting on new international regulations related to ozone layer (Armenia) 15. Hotline receives over 50 illegal activity reports